A usability study on content display in mobile learning / Riaza Rias, Fazilah Ismail and Azlan Ismail - Rias, Riaza; Ismail, Fazilah; Ismail, Azlan (Penerbit UiTM (UiTM Press), 2009)
Mobile technology has started to play many important roles in our lives. In education, mobile technology could assist learning while students are on the move by using mobile devices such as personal digital assistant (PDA), mobile phones or a laptop. We look at PDAs in this study. One of the problems faced by small devices are the way to display information on a small screen size. A navigation technique is implemented to display the content for learning programming in C++ on a PDA. A usability study is also conducted on the prototype design using QUIS guidelines on 10 students. We discuss the results of the usability study.